Antiviral Molecular Targets of Essential Oils against SARS-CoV-2: A Systematic Review - Muhammad Iqhrammullah; Diva Rayyan Rizki; Agnia Purnama; Teuku Fais Duta; Harapan Harapan; Rinaldi Idroes; Binawati Ginting (MDPI AG, 2023)
Essential oils are potential therapeutics for coronavirus disease 2019 (COVID-19), in which some of the volatile compounds of essential oils have been well known for their broad antiviral activities. These therapeutic candidates have been shown to regulate the excessive secretion of pro-inflammatory cytokines, which underlies the pathogenesis of severe COVID-19. We aimed to identify molecular targets of essential oils in disrupting the cell entry and replication of SARS-CoV-2, hence being active as antivirals. Literature searches were performed on PubMed, Scopus, Scillit, and CaPlus/SciFinder (7 December 2022) with a truncated title implying the anti-SARS-CoV-2 activity of essential oil. Data were collected from the eligible studies and described narratively. Quality appraisal was performed on the included studies. A total of eight studies were included in this review; four of which used enzyme inhibition assay, one-pseudo-SARS-CoV-2 culture; two-whole SARS-CoV-2 culture; and one-ACE2-expressing cancer cells. Essential oils may prevent the SARS-CoV-2 infection by targeting its receptors on the cells (ACE2 and TMPRSS2). Menthol, 1,8-cineole, and camphor are among the volatile compounds which serve as potential ACE2 blockers. β-caryophyllene may selectively target the SARS-CoV-2 spike protein and inhibit viral entry. Other interactions with SARS-CoV-2 proteases and RdRp are observed based on molecular docking. In conclusion, essential oils could target proteins related to the SARS-CoV-2 entry and replication. Further studies with improved and uniform study designs should be carried out to optimize essential oils as COVID-19 therapies.